Ca2+-Dependent Transcriptional Repressors KCNIP and Regulation of Prognosis Genes in Glioblastoma - Néant, Isabelle; Haiech, Jacques; Kilhoffer, Marie-Claude; Aulestia, Francisco J.; Moreau, Marc; Leclerc, Catherine (Frontiers in Molecular Neuroscience, 2018)
Glioblastomas (GBM) are the most aggressive and lethal primary astrocytic tumors in adults, with very poor prognosis. Recurrence in GBM is attributed to Glioblastoma Stem-Like Cells (GSLCs). The behavior of the tumor, including the proliferation, progression, invasion and significant resistance to therapies, is a consequence of the self-renewing properties of the GSLCs and their high resistance to chemotherapies have been attributed to their capacity to enter quiescence. Thus, targeting GSLCs may constitute one of the possible therapeutic challenges to significantly improve anti-cancer treatment regimens for GBM. Ca2+ signaling is an important regulator of tumorigenesis in GBM and the transition from proliferation to quiescence involved the modification of the kinetics of Ca2+ influx through store-operated channels due to an increased capacity of the mitochondria of quiescent GSLC to capture Ca2+. Therefore, the identification of new therapeutic targets requires the analysis of the calcium regulated elements at transcriptional levels. In this review we focus onto the direct regulation of gene expression by KCNIP proteins (KCNIP1-4). These proteins constitute the class E of Ca2+ sensor family with 4 EF-hand Ca2+-binding motifs and control gene transcription directly by binding, via a Ca2+-dependent mechanism, to specific DNA sites on target genes, called Downstream Regulatory Element (DRE). The presence of putative DRE sites on genes associated with unfavorable outcome for GBM patients suggests that KCNIP proteins may contribute to the alteration of the expression of these prognosis genes. Indeed, in glioblastoma KCNIP2 expression appears to be significantly linked to the overall survival of patients. In this review we summarize the current knowledge regarding the quiescent GSLCs with respect to Ca2+ signaling and discuss how Ca2+ via KCNIP proteins may affect prognosis genes expression in GBM. This original mechanism may constitute the basis of the development of new therapeutic strategies.